YES Problem: c(b(a(a(x1)))) -> a(a(b(c(x1)))) b(a(a(a(x1)))) -> a(a(a(b(x1)))) a(b(c(x1))) -> c(b(a(x1))) c(c(b(b(x1)))) -> b(b(c(c(x1)))) Proof: String Reversal Processor: a(a(b(c(x1)))) -> c(b(a(a(x1)))) a(a(a(b(x1)))) -> b(a(a(a(x1)))) c(b(a(x1))) -> a(b(c(x1))) b(b(c(c(x1)))) -> c(c(b(b(x1)))) Matrix Interpretation Processor: dim=3 interpretation: [1 1 0] [c](x0) = [0 1 0]x0 [0 0 1] , [0] [b](x0) = x0 + [0] [1], [1 0 1] [0] [a](x0) = [0 1 0]x0 + [1] [0 0 1] [0] orientation: [1 1 2] [2] [1 1 2] [2] a(a(b(c(x1)))) = [0 1 0]x1 + [2] >= [0 1 0]x1 + [2] = c(b(a(a(x1)))) [0 0 1] [1] [0 0 1] [1] [1 0 3] [3] [1 0 3] [0] a(a(a(b(x1)))) = [0 1 0]x1 + [3] >= [0 1 0]x1 + [3] = b(a(a(a(x1)))) [0 0 1] [1] [0 0 1] [1] [1 1 1] [1] [1 1 1] [1] c(b(a(x1))) = [0 1 0]x1 + [1] >= [0 1 0]x1 + [1] = a(b(c(x1))) [0 0 1] [1] [0 0 1] [1] [1 2 0] [0] [1 2 0] [0] b(b(c(c(x1)))) = [0 1 0]x1 + [0] >= [0 1 0]x1 + [0] = c(c(b(b(x1)))) [0 0 1] [2] [0 0 1] [2] problem: a(a(b(c(x1)))) -> c(b(a(a(x1)))) c(b(a(x1))) -> a(b(c(x1))) b(b(c(c(x1)))) -> c(c(b(b(x1)))) String Reversal Processor: c(b(a(a(x1)))) -> a(a(b(c(x1)))) a(b(c(x1))) -> c(b(a(x1))) c(c(b(b(x1)))) -> b(b(c(c(x1)))) Matrix Interpretation Processor: dim=3 interpretation: [1 1 0] [c](x0) = [0 0 1]x0 [0 1 0] , [1 1 0] [0] [b](x0) = [0 0 0]x0 + [0] [0 1 1] [1], [1 0 0] [a](x0) = [0 1 1]x0 [0 0 0] orientation: [1 1 1] [0] [1 1 1] [0] c(b(a(a(x1)))) = [0 1 1]x1 + [1] >= [0 1 1]x1 + [1] = a(a(b(c(x1)))) [0 0 0] [0] [0 0 0] [0] [1 1 1] [0] [1 1 1] [0] a(b(c(x1))) = [0 1 1]x1 + [1] >= [0 1 1]x1 + [1] = c(b(a(x1))) [0 0 0] [0] [0 0 0] [0] [1 2 1] [2] [1 2 1] [0] c(c(b(b(x1)))) = [0 0 0]x1 + [0] >= [0 0 0]x1 + [0] = b(b(c(c(x1)))) [0 1 1] [2] [0 1 1] [2] problem: c(b(a(a(x1)))) -> a(a(b(c(x1)))) a(b(c(x1))) -> c(b(a(x1))) String Reversal Processor: a(a(b(c(x1)))) -> c(b(a(a(x1)))) c(b(a(x1))) -> a(b(c(x1))) Matrix Interpretation Processor: dim=2 interpretation: [1 1] [c](x0) = [0 1]x0, [1 0] [1] [b](x0) = [0 2]x0 + [2], [2 0] [1] [a](x0) = [0 1]x0 + [0] orientation: [4 4] [7] [4 2] [6] a(a(b(c(x1)))) = [0 2]x1 + [2] >= [0 2]x1 + [2] = c(b(a(a(x1)))) [2 2] [4] [2 2] [3] c(b(a(x1))) = [0 2]x1 + [2] >= [0 2]x1 + [2] = a(b(c(x1))) problem: Qed